ANALISIS TEGANGAN PADA BALOK TERLENTUR DUA TUMPUAN DENGAN METODA PHOTOELASTISITAS - Puspantoro, Benny
Experimental stress analysis by photoetastic method has been used to obtain stress pat terrz.s that known. as isochromatics and isoclinics in a model. study. In transferring the results from a\'transparant model, called \' Araldit\', to a structural prototype, such as steel, care must be taken to ascertain that the Loads on the model are in reality the same as those on the prototype. Stresses in prototype can be determined using dimensional analysis. Photoelastic\' methods is based on the theory of elasticity and basic optic, and referred to refraction in.. a material model. There are two methods of photoelasticity,-i.e. : Two Dimensional Photoelasticity and Three Dimensional Photoelasticity. The important equipment is : AnaLizer and Polarizer. Here we only discuss Two Dimensional Photoelasticity. The prototype is a Plate Girder as a simply supported beam Bending stresses resulted of the photoeLastic investigations wiLL be compared with the beam theory and finite element analysis.